Phytochemical content, antioxidant activity and mineral elements of honey produced by four different species of Malaysian stingless bees - Bernard, Maringgal; Hashim, N.; Tawakkal, I.S.M.A.; Mohamed, M.T.M.; Hamzah, M.H. (2021)
This study investigated the phytochemical composition of honey from four species of Malaysian stingless bee i,e. Tetragonula laeviceps, Geniotrigona thoracica, Lepidotrigona terminata, as well as Heterotrigona itama. The measured phytochemical composition was total phenolic content (TPC), total flavonoid content (TFC), antioxidant activity, pH, colour intensity, and mineral element analysis i.e. Magnesium (Mg), Calcium (Ca), Zinc (Zn), Potassium (K), and Sodium (Na). The production of honey by the L. terminata had the highest TPC value (6.74±0.57 mg GAE/100 g FW) while the T. laeviceps possesses the highest TFC value (14.85±3.71 mg QE/100 g FW). In the antioxidant activity measurement, honey from the H. itama obtained the highest percentage of 1,1-diphenyl-2- picrylhydrazyl (DPPH) inhibition (29.52±0.45%) and honey from T. laeviceps displayed the highest value in the Ferric reducing antioxidant power (FRAP) analysis (0.95±0.013 abs). The four distinct stingless bee species’ colour intensity demonstrated the variation of colour intensity in the range of 0.09-0.23 abs mAU. All honey obtained the pH values (4.75-5.03) within the acidic medium. Mg is the major mineral element in all honey samples which is followed by Na, Ca, K, and Zn.